Use of mundane analogies as an effective tool for teaching and learning - A. Manan, Zainuddin; Muis, Zarina (2005)
This paper describes the use of mundane analogies as an effective tool for teaching and learning particularly in chemical engineering subjects that are full with chemical concepts and methods that are complex and may be difficult to understand.